Fixed/Prescribed-Time Synchronization of Fuzzy Inertial Memristive Neural Networks With Time-Varying Delay: Interval Matrix Method and PI Control - Xin Ya Wang; Qing Zhang; Guici Chen (IEEE Access)
This paper investigates the fixed/prescribed-time synchronization issues for fuzzy inertial memristive neural networks (FIMNNs) with time-varying delay, which integrate fuzzy logic, inertial terms, memristors, and time-varying delays simultaneously. The interval matrix method is employed firstly to deal with the state-dependent switching parameters, which is distinguished from the existing maximum absolute value approach. Consequently, the FIMNNs with time-varying delay are transformed into a type of delayed fuzzy systems, with coefficients characterized by a series of interval matrices. Following this, within the framework of Filippov solutions and differential inclusions, fixed/prescribed-time synchronization is comprehensively discussed. Two novel PI feedback controllers are synthesized through the resolution of a series of linear matrix inequalities (LMIs), followed by numerical simulations to demonstrate their effectiveness.